Polymer-coated nanoparticles and method for producing same
Through polymer-coated nanoparticle technology, nanoparticles with polymer shell are formed using cationic and anionic components, solving the problems of low encapsulation rate and poor stability of water-soluble drugs, and achieving efficient and stable drug packaging and release.
Patent Information
- Application Number
- JP2024553624
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-07
- Filing Date
- 2023-03-07
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to effectively develop a high encapsulation rate and stability of the nano-drug carrier system for water-soluble drugs, especially high water-soluble drugs such as polypeptide drugs.
Using polymer-coated nanoparticles technology, nanoparticles with polymer shell are formed by combining a positively charged or ionizable charge with a negatively charged anionic component. The polymer shell contains polyoxyethylene structural units, which accurately controls liquid flow and mixing through microflower mixing technology to ensure consistent particle size distribution and high encapsulation rate.
A water-soluble drug-inherited carrier system with high packaging rate (packaging rate >60%) and good stability is achieved, which improves the efficacy and safety of the drug, while simplifying the production process and improving batch repeatability.
Smart Images

Figure 2025509367000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention claims priority to a Chinese patent application with application number 202210216401.5, titled "Polymer-coated nanoparticles and their preparation method", filed with the China Patent Office on March 7, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention belongs to the technical field of drug formulations, and specifically relates to polymer-coated nanoparticles and a method for preparing the same. [Background technology]
[0003] Common technology types of nano-formulations include liposomes, micelles, nanoparticles, microspheres, etc. At present, drug loading technologies for poorly water-soluble drugs are relatively mature, including structural modification, amphoteric surfactant micelle nanoparticles, liposome passive drug loading, etc. However, nano-drug loading technologies for water-soluble drugs are relatively limited, for example, the permeability of the liposome membrane directly affects the encapsulation and stability of drugs, and the solubility and ionization properties of drugs are severely limited by various types of technologies. There is still a lack of effective and versatile nano-drug loading technologies for water-soluble drugs.
[0004] Liposomes are spherical, closed sacs formed by phospholipids that encapsulate a portion of the aqueous phase. The liposome structure usually contains two layers of phospholipid membranes that separate the internal aqueous space from the outside world, and the particle size ranges from 20 nm to several tens of microns. Among the liposomal drugs currently on the market, only a few are water-soluble drugs. Doxorubicin liposomes (Doxil®), vincristine liposomes (Marqibo®), irinotecan liposomes (Onivyde®) and daunorubicin-cytarabine liposomes (Vyxeos®) have been approved for clinical indications such as antitumor. These liposomes employ active drug loading preparation methods such as pH gradient drug loading method / ammonium salt gradient method, which utilizes a transmembrane gradient to load water-soluble drug molecules into the liposomes. The properties of encapsulated water-soluble drugs are subject to strict requirements, such as having a dissociable group near physiological pH, having an appropriate oil-water partition coefficient, being a weak acid or base, and being able to form a relatively stable complex or precipitate with the internal buffer solution of the liposome (Non-Patent Document 1).
[0005] Polymeric micelles (micelles) are spherical structures assembled from amphiphilic molecules or surfactants (including ionic or nonionic surfactants) that contain hydrophilic and hydrophobic ends, and encapsulate hydrophobic drugs in the core. Currently, anticancer drug micelles such as paclitaxel and doxorubicin are in clinical trials or are commercially available. Compared with liposomes, polymeric micelles can encapsulate many hydrophobic drugs in the hydrophobic core, but it is difficult to encapsulate hydrophilic drugs.
[0006] Nanoparticles include paclitaxel-albumin nanoparticles, which are nanoparticles formed by combining paclitaxel with the biopolymer albumin as a carrier material. Although this has shown good clinical results, it still faces challenges due to strict preparation requirements and difficulties in industrialization.
[0007] Microspheres are tiny spheres or spheroids formed by dissolving or dispersing drugs in polymeric materials, and their particle size is usually in the range of 1-250 μm. Commonly used polymeric materials are water-insoluble biodegradable polymers such as polylactic acid (PLA) and polylactic acid-hydroxyacetic acid copolymer (PLGA). Due to the limitations of the encapsulation process, it is difficult to prepare water-soluble drug nanoparticles with particle sizes less than 200 nm. [Prior art documents] [Non-patent literature]
[0008] [Non-Patent Document 1] "Liposome Technology" by Tang Yujie, People's Medical Press, January 2007 Summary of the Invention [Problem to be solved by the invention]
[0009] Taking the nanoformulation of water-soluble peptide polymyxin as an example, the application of polymyxin liposomes is limited due to its low encapsulation rate. In conventional technology, the encapsulation rate of liposomes is only less than 50%, and polymyxin liposomes leak rapidly when the drug is diluted. The reasons why it is difficult to prepare polymyxin liposomes with a high encapsulation rate are: (1) the liposome membrane is a semipermeable membrane with fluidity, and water-soluble components easily pass through the phospholipid membrane, and (2) the liposome membrane has nonselective permeability to many types of ions, so active drug loading methods based on ion concentration are not suitable for encapsulation and loading of polymyxin.
[0010] Polymer nanoparticles (e.g., polylactic acid) are important peptide nanocarriers that can be used to prepare local sustained-release nano drug delivery systems for antimicrobial peptides. Since polymyxin is highly water-soluble, during the encapsulation and loading process of polymer nanoparticles, polymyxin quickly diffuses into the external aqueous phase, resulting in a very low encapsulation rate of polymyxin in polymer nanoparticles.
[0011] Currently, many nanoparticle platforms are used to develop water-soluble drugs, including liposomes, polymeric nanoparticles, etc. However, they often encounter the same common problems as water-soluble drug nanoformulations, namely low encapsulation rate, low stability, or reduced drug activity.
[0012] The nano-drug loading systems included in the disclosed technology are mainly prepared by thin film dispersion, reverse phase evaporation, or high pressure homogenization, and most of the microparticles prepared are liposomes or nanoparticles, which cannot simultaneously achieve properties such as uniform particle size distribution, high encapsulation rate, good stability, effective drug release, improved efficacy, and reduced toxicity. Therefore, in order to improve efficacy and enhance drug safety, it is extremely important to develop a new nanocarrier system with high encapsulation rate and uniform particle size distribution for drug delivery. [Means for solving the problem]
[0013] Contents of the invention In order to solve the above technical problems, the present invention provides a polymer-coated nanoparticle and a preparation method thereof, which can effectively improve the efficacy of drugs and enhance the safety of drugs.
[0014] To achieve the above objectives, the technical solution provided by the present invention is as follows:
[0015] The polymer-coated nanoparticles have a composition structure consisting of a hydrophilic aggregate core and a coating of a polymer molecular material containing polyoxyethylene structural units, the hydrophilic aggregate core containing a cationic component and an anionic component as raw materials for production, the cationic component being a cation or a compound ionizable to a cation or a composition thereof, and the anionic component being an anion or a compound ionizable to an anion or a composition thereof.
[0016] Preferably, the nanoparticles have a particle size of 10-400 nm, a PDI<0.5, preferably 10-200 nm, a weakly charged or neutral surface, a surface potential range of -40 mV to 40 mV, and an encapsulation rate of >60%.
[0017] Preferably, the nanoparticles have an encapsulation rate >60%, preferably >70%.
[0018] Preferably, the cationic compound or composition thereof is any one or more of a hydrophilic small molecule compound, a polypeptide, a polymer, and a phospholipid that is ionizable or has a net positive charge.
[0019] Preferably, the polypeptide is a hydrophilic polypeptide having an ionizable or net positive charge and a molecular weight of <10,000.
[0020] Preferably, the polypeptide comprises one or more of ionizable hydrophilic polypeptides and derivatives thereof with a cyclic structure containing a free amine group, ionizable hydrophilic polypeptides and derivatives thereof with a molecular weight <10,000 and free primary amine, secondary amine, or tertiary amine structures, as well as polylysine and its derivatives, polyarginine and its derivatives, polyhistidine and its derivatives, and arginine-rich polypeptides.
[0021] Preferably, the polypeptide is selected from the group consisting of polymyxin and its derivatives, vancomycin, tigecycline, capreomycin, teicoplanin, daptomycin, caspofungin, micafungin, glucagon, exenatide, pramlintide, dulaglutide, liraglutide, semaglutide, albiglutide, insulin, romidepsin, actinomycin, gonadorelin, bleomycin, leuprorelin, goserelin, hitorelin, triptorelin, buserelin, epsin, seroton ... One or more of tifibatide, icatibant, nesiritide, octreotide, linaclotide, somatostatin, terlipressin, atosiban, carbetocin, oxytocin, lysine vasopressin, vasopressin, desmopressin, cobicistat, thymopentin, glutathione, enfuvirtide, thymalfasin, tesamorelin, glatiramer acetate, bivalirudin, ziconotide, pasireotide, etelcalcetide, teriparatide, and abaloparatide.
[0022] Preferably, the polymyxin and derivatives thereof include any one or more of polymyxin B sulfate, polymyxin E, polymyxin E1, polymyxin E2 and polymyxin E sodium methanesulfonate, polymyxin colistin E1 sodium methanesulfonate and polymyxin E2 sodium methanesulfonate.
[0023] Preferably, the ionizable or positively charged hydrophilic small molecule compound is an ionizable or positively charged hydrophilic compound that contains an amine group structure.
[0024] Preferably, the hydrophilic small molecule compound having an ionizable or positive net charge is one or more of metal complexes and derivatives thereof, ionizable hydrophilic anesthetic / analgesic drugs having an amine group structure, ionizable hydrophilic psychotropic drugs having an amine group structure, and ionizable hydrophilic anticancer / antitumor drugs having an amine group structure and derivatives thereof.
[0025] Preferably, the hydrophilic small molecule compound having an ionizable or positive net charge is lenalidomide, pomalidomide, dabrafenib, carfilzomib, acalabrutinib, palbociclib, trametinib, bortezomib, ruxolitinib, imatinib, sunitinib, axitinib, ribociclib, capecitabine, osimertinib, minoxidil, primidone, procainamide hydrochloride, flecainide, phenytoin sodium, guanethidine sulfate, isoproterenol sulfate, clindamycin hydrochloride, clonidine hydrochloride, theophylline, aminophylline, quinidine sulfate, metformin, alogliptin, saxagliptin, linagliptin, vildagliptin, teneligliptin, hydrochlorothiazide, hydralazine, labeline, cefolia ... Tallol, metoprolol, clonidine, nicardipine, esmolol, torsemide, valsartan, diltiazem, phentolamine, salbutamol, salmeterol, lacosamide, tiotropium bromide, olanzapine, levetiracetam, methylphenidate, bupropion, brivaracetam, lamotrigine, cariprazine, chlorpromazine, haloperidol, risperidone, quetiapine, citalopram, paliperidone palmitate, mirtazapine, chlormezadone, pregabalin, parecoxib, bupivacaine, pentazocine, butorphanol, naloxone, codeine, pethidine, fentanyl, dihydroetorphine, tramadol, morphine, ketorolac tromethamine, remdesivir, emtricitabine, tenofovir The drugs include one or more of disoproxil, lamivudine, amikacin sulfate, imipenem, darunavir, clavulanic acid, fingolimod, lisdexamfetamine mesylate, benserazide, droxidopa, metaiodobenzylguanidine, iopromide, iohexol, carboplatin, cisplatin, oxaliplatin, cyclohexanediamine platinum dinitrate, cyclohexanediamine platinum dihydrate, omaplatin and other platinum complexes and derivatives thereof, ruthenium(II) complexes and derivatives thereof, vanadium complexes and derivatives thereof, cetrimonium bromide, imidazolidinyl urea, methylglucamine derivatives, and triethanolamine derivatives.
[0026] Preferably, the polymer is hydrophilic and is one or more of an ionizable hydrophilic polymer containing amine, guanidine or imine groups in the side chains or main chain, and a cationic polysaccharide.
[0027] Preferably, the polymer is one or more of polyethyleneimine (PEI), polyamidoamine (PAMAM), polyurethane, polyamine coester, chitosan and its derivatives, and povidone.
[0028] Preferably, the phospholipid is one or more of cationic lipids and derivatives thereof containing a quaternary ammonium group, a pyridyl group, a guanidinyl group, or an imidazolyl group in the hydrophilic head group, ionizable lipids and derivatives thereof containing an amine structure in the hydrophilic head group, polyethyleneimine-phospholipids and derivatives thereof, and 3β-[N-(N',N'-dimethylaminoethyl)carbamoyl]cholesterol hydrochloride (DC-CHOL) and derivatives thereof.
[0029] Preferably, the anionic compound or composition thereof is one or more of ionizable or anionic hydrophilic small molecule compounds, ionizable or anionic hydrophilic mono- or oligosaccharide acids and derivatives thereof, ionizable or anionic hydrophilic polysaccharides and derivatives thereof, anionic polyamino acids and derivatives thereof, and nucleic acids.
[0030] Preferably, the mono- or oligosaccharide acids and derivatives thereof include any one or more of sulfated glucose, sulfated fructose, phosphorylated glucose, phosphorylated fructose, sulfated sucrose, sulfated lactose, sulfated trehalose, phosphorylated sucrose, phosphorylated lactose and phosphorylated trehalose.
[0031] Preferably, the polysaccharide and its derivative are one or more of glycosaminoglycans, cellulose-based polysaccharides, polyuronic acid-based polysaccharides, galactomannan polysaccharides, and derivatives thereof.
[0032] Preferably, the polysaccharides and derivatives thereof are any one or more of sodium hyaluronate, cross-linked sodium hyaluronate, chondroitin sulfate, dermatan sulfate, keratan sulfate, heparin sodium, heparan sulfate, dalteparin sodium, enoxaparin sodium and fondaparinux.
[0033] Preferably, the polysaccharide and its derivatives are one or more of cellulose acetate, sodium carboxymethylcellulose, hydroxyethylcellulose, hydroxyethylmethylcellulose, hydroxypropylcellulose and hypromellose.
[0034] Preferably, the polysaccharides and derivatives thereof are any one or more of polyglucuronic acid, polyfurfural acid, sodium polymannuronate, sodium polyguluronic acid, alginic acid, sodium alginate, propylene glycol alginate, xanthan gum, tragacanth, gum arabic and carrageenan.
[0035] Preferably, said nucleic acid is a ribonucleic acid or a deoxyribonucleic acid.
[0036] Preferably, the nucleic acid is an siRNA, an mRNA, an miRNA, an antisense oligonucleotide, a DNA, a circular RNA, or a tRNA.
[0037] Preferably, the polyoxyethylene structural unit is -(CH2CH2O)n (n=6 to 460).
[0038] Preferably, the polymer molecule material containing a polyoxyethylene structural unit is one or more of PEG-phospholipid, PEG-cholesterol, PEG-polymer, polysorbate, polyoxyethylene castor oil and its derivatives, and polyoxyethylene stearate.
[0039] Preferably, the polymeric material comprising polyoxyethylene structural units is any one or more of polyethylene glycol, polyethylene glycol-polylactic acid, polyethylene glycol-polylactic acid-glycolic acid polymer, polyethylene glycol-polyglutamic acid, polyglutamic acid-polyethylene glycol-carboxylic acid, polyethylene glycol-distearoylphosphatidylethanolamine, polyethylene glycol-dimyristoyl-sn-glycerol, polyethylene glycol-distearoylglycerol, polyethylene glycol-dimyristoylphosphatidylethanolamine, polyethylene glycol-dipalmitoylglyceryl, polyethylene glycol-dipalmitoylphosphatidylethanolamine, polyethylene glycol-dilauroylphosphatidylethanolamine, polyethylene glycol dipalmitoylphosphatidylserine, polyethylene glycol-dioleoylphosphatidylethanolamine, polyethylene glycol-cholesterol, and cholesterol-polyethylene glycol-VA.
[0040] Preferably, the cationic moiety comprises any one or more of polymyxin and its derivatives, platinum complexes and its derivatives, ruthenium(II) complexes and its derivatives, vanadium complexes and its derivatives, DC-cholesterol and its derivatives, chitosan hydrochloride and its derivatives, polyethyleneimine hydrochloride and its derivatives, poly-L-arginine hydrochloride and its derivatives, DOTAP ((2,3-dioleoyl)-trimethylammonium chloride), DOTMA (dioleoylpropyltrimethylammonium chloride), thymalfasin, octreotide acetate, liraglutide, pasireotide, risperidone hydrochloride, clonidine hydrochloride, methylphenidate, brivaracetam, levetiracetam, pregabalin, bortezomib, imatinib, palbociclib, daptomycin, vancomycin, tigecycline, imipenem, clindamycin hydrochloride and amikacin sulfate.
[0041] Preferably, the anionic component comprises one or more of polyglutamic acid polypeptides and derivatives thereof, polyaspartic acid polypeptides and derivatives thereof, hyaluronate, sucrose octasulfate, sodium alginate, xanthan gum, CMC-Na, siRNA, mRNA, sodium sulfadiazine, and sodium carboxymethylcellulose.
[0042] Preferably, the polymeric material comprising polyoxyethylene structural units comprises one or more of distearoylphosphatidylethanolamine-methoxypolyethylene glycol, PEG-PLA (polyethylene glycol polylactic acid block copolymer), 1,2-dimyristoyl-rac-glycerol-3-methoxypolyethylene glycol, polyethylene glycol-polylactic acid-glycolic acid polymer, polyglutamic acid-polyethylene glycol-carboxylic acid, polysorbate, polyoxyethylene castor oil, polyoxyethylene stearate, polyethylene glycol-polyglutamic acid, polyethylene glycol-glyceryl dipalmitate, polyethylene glycol-dipalmitoylphosphatidylethanolamine, polyethylene glycol-dimyristoylphosphatidylethanolamine, polyethylene glycol-dilauroylphosphatidylethanolamine, polyethylene glycol-dipalmitoylphosphatidylserine, polyethylene glycol-cholesterol, cholesterol-polyethylene glycol-VA.
[0043] Preferably, the charge ratio of the cationic component to the anionic component in the nanoparticles is 1-8:1-10.
[0044] Preferably, the weight percentage of the hydrophilic aggregate core in said nanoparticles is between 1% and 90%, preferably between 5% and 80%.
[0045] Another object of the present invention is to (1) preparing an aggregate solution by dissolving and mixing a cationic component and an anionic component; (2) preparing a coating solution by dissolving a polymer molecule material containing polyoxyethylene structural units; (3) mixing the aggregate solution and the coating solution to prepare a polymer-coated nanoparticle solution; The present invention provides a method for producing nanoparticles comprising the steps of:
[0046] Preferably, the polymer-coated nanoparticle solution can be further filtered and / or purified.
[0047] Preferably, in the method for producing nanoparticles, the aggregate solution is a homogeneous solution.
[0048] Preferably, in the method for producing nanoparticles, the mixing is performed by a microchannel mixing method, and the microchannel mixing method is performed by an injection technique, a microfluidics technique or a jet flow technique.
[0049] Preferably, in the preparation method, the mixing volume ratio of the aggregate solution to the coating solution is 1-10:1-20, and more preferably 1-8:1-10.
[0050] Preferably, the mixing speed of the microchannel mixer is 0.5 to 400 ml / min.
[0051] Preferably, in said method for preparing nanoparticles, the injection technique is to inject the aggregate solution into the coating solution, or to inject the coating solution into the aggregate solution.
[0052] Preferably, the nanoparticles are stored lyophilized.
[0053] Another object of the present invention is to provide a formulation of said nanoparticles, which are structurally characterized by having a hydrophilic aggregate core containing an active ingredient and a polymer molecular coating containing polyoxyethylene structural units, the encapsulation rate of the nanoparticles being >60%, the average particle size being 10-400 nm, the surface being weakly electric or neutral, and the surface potential range being -40 mV to 40 mV.
[0054] Preferably, the nanoparticle formulation contains an excipient commonly used in pharmacy, and the excipient includes one or more of potassium dihydrogen phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, dipotassium hydrogen phosphate, sodium chloride, potassium chloride, sodium acetate, acetic acid, sucrose, mannitol, lactose, glucose, trehalose, polyethylene glycol, glycerin, phosphate, acetate, amino acid, water for injection, 0.5 to 0.9% sodium chloride aqueous solution (preferably 0.9% sodium chloride aqueous solution), 1 to 5% glucose aqueous solution (preferably 5% glucose aqueous solution), and PBS buffer solution.
[0055] Routes of administration of the nanoparticle formulations provided herein include subcutaneous, intradermal, intramuscular, intraarticular, intrathoracic, intraspinal, intralesional, intracranial, intravenous injection and any suitable infusion method, as well as pulmonary administration.
[0056] Compared with the prior art, the technical advantages of the present invention are as follows:
[0057] (1) The present invention provides nanoparticle preparations with good performance, and the selection of materials in such nanoparticle formulations has a certain effect on the encapsulation rate, particle size, morphology, in vivo stability, drug release rate, efficacy and toxicity of nanoparticles.
[0058] (2) Commonly used nano drug delivery systems (such as liposomes, micelles, inorganic nanoparticles, polymer nanoparticles, etc.) are usually prepared by thin film dispersion, reverse phase evaporation, or high pressure homogenization. When the preparation process includes a mixing step, the preparation is often carried out by the principle of macrofluid interaction, but the preparation process is complicated and the structure may differ from batch to batch, resulting in non-uniform particle distribution of the nanoparticles and poor dispersion and reproducibility. The present invention utilizes microchannel mixing technology to precisely control the flow rate and flow rate of the fluid, so that the liquid components introduced at different times are thoroughly mixed and highly uniform and regular, so that the prepared nanoparticles show obvious advantages in terms of uniformity of particle structure, batch reproducibility and drug encapsulation rate.
[0059] (3) Compared with the prior art (nano preparations such as liposomes, micelles, and microspheres), the nanoparticles of the present invention and the preparation method thereof provide spherical nanoparticles comprising a hydrophilic aggregate core formed from a hydrophilic active ingredient and a hydrophilic polymer material, and a coating shell formed by adding a hydrophilic amphiphilic polymer material containing a polyoxyethylene structure. The hydrophilic aggregate core forms hydrophilic aggregates due to intermolecular forces including charge interactions (Coulomb's law), steric effects, etc. Such hydrophilic aggregates are a uniform solution macroscopically, but are in a liquid-liquid phase separation state microscopically.
[0060] (4) The nanoparticles provided by the present invention maintain the efficacy of free hydrophilic drugs while significantly improving their safety.
[0061] (5) The nanoparticle preparation process provided by the present invention adopts a precise mixing process of aqueous solutions, and does not require the use of traditional nanoparticle preparation processes such as organic solvent membrane dispersion method and high-pressure homogenization. The process is simple, has good reproducibility, and is easy to commercialize. [Brief description of the drawings]
[0062] [Figure 1]1 shows the hydrophilic aggregate core solution (left) and the polymer-coated nanoparticle solution (right) in Example 1. [Diagram 2] 1 is a transmission electron microscope image of the polymer-coated nanoparticles in Example 4. [Diagram 3] FIG. 2 is a graph showing the average particle size of the polymer-coated nanoparticles in Example 1. [Figure 4] FIG. 13 is a graph showing the average particle size of polymer-coated nanoparticles in Example 4. [Diagram 5] FIG. 13 is a graph showing the average particle size of the polymer-coated nanoparticles in Example 8. [Figure 6] FIG. 13 is a graph showing the average particle size of the polymer-coated nanoparticles in Example 12. [Figure 7] 1 shows the surface potential of the polymer-coated nanoparticles in Example 5. [Figure 8] 13 is a surface potential of the polymer-coated nanoparticles in Example 8. [Figure 9] 13 is a surface potential of the polymer-coated nanoparticles in Example 10. [Figure 10] 1 is a release curve of an active ingredient in polymer-coated nanoparticles. [Figure 11] 1 is a safety test of the polymer-coated nanoparticles in Examples 1 and 2: MTD chart. [Figure 12] 1 is a safety test of the polymer-coated nanoparticles in Example 3: MTD chart. [Figure 13] 1 is an antibacterial test of polymer-coated nanoparticles: MIC chart. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0063] The present invention will be described in more detail below with reference to specific examples, but the following examples are not intended to limit the present invention and are only used to illustrate the present invention. Unless otherwise specified, the experimental methods used in the following examples are generally in accordance with conventional conditions, unless otherwise specified. Materials, reagents, etc. used in the following examples are commercially available, unless otherwise specified. EXAMPLES
[0064] Preparation method: 20 mg of colistin sulfate and 32 mg of polyglutamic acid were dissolved in 10 ml of water to obtain solution 1. 600 mg of mPEG5000-DSPE (distearoylphosphatidylethanolamine-methoxypolyethyleneglycol5000) was dissolved in 30 ml of water to obtain solution 2. Solution 1 was injected into solution 2 at a rate of 12 ml / min and mixed, and the mixed solution was sterile filtered to obtain colistin polymer-coated nanoparticles.
[0065] Detection method: Malvern ZetaSizer Nano ZS90 was used to measure the average particle size and polydispersity index PDI of the polymer-coated nanoparticles of the examples by dynamic light scattering, the measurement angle was 90°, the refractive index of the dispersant was 1.330, and the test temperature was 25°C.
[0066] The zeta potential of the polymer-coated nanoparticles in the examples was measured based on electrophoretic light scattering technique (ELS) using a Malvern ZetaSizer Nano ZS90. Refractive index of dispersant: 1.330, test temperature: 25°C.
[0067] 2.5 ml of the polymer-coated nanoparticle solution of the embodiment was taken, loaded into an ultrafiltration centrifuge tube (Amicon Ultra-4 Centrifugal Filters, molecular weight cutoff 30 kD), centrifuged at 5000 rpm / min, and the amount of free drug in the centrifuge tube and the amount of encapsulated drug fractionated on the filter were measured by the HLPC method. Measurements were performed using 4.46 g / L sodium sulfate solution (pH 2.4)-acetonitrile (78:22) as the mobile phase, with a detection wavelength of 215 nm, a flow rate of 1.0 ml / min, and an injection volume of 20 μl, and the amount of fractionated drug was 1.2484 mg and the amount of free drug was 0.0044630 mg. (The formula for calculating the encapsulation rate is encapsulation rate (EE%) = amount of fractionated drug / (amount of fractionated drug + amount of free drug) × 100%), and the results are shown in Table 3 below. EXAMPLES
[0068] Preparation method: 15 mg of polymyxin B sulfate and 54 mg of sodium carboxymethylcellulose were dissolved in 20 ml of water to obtain solution 1. 186 mg of polyoxyethylene stearate was dissolved in 10 ml of water to obtain solution 2. Using a microfluidics device, solutions 1 and 2 were mixed at a rate of 20 ml / min. The mixed solution was sterilized and filtered to obtain polymyxin B polymer-coated nanoparticles.
[0069] Detection method: As a result of measurement in the same manner as in Example 1, the amount of fractionated drug was 1.2074 mg, and the amount of free drug was 0.032871 mg. The results are shown in Table 3 below. EXAMPLES
[0070] Preparation method: 20 mg of cyclohexanediamineplatinum dihydrate and 72 mg of sodium hyaluronate were dissolved in 10 ml of water to obtain solution 1. 208 mg of PEG-cholesterol was dissolved in 30 ml of water to obtain solution 2. Using a microfluidic device, solutions 1 and 2 were mixed at a rate of 9 ml / min. The mixed solution was sterilized and filtered to obtain cyclohexanediamineplatinum dihydrate polymer-coated nanoparticles.
[0071] Detection methods: The methods for detecting the particle size, PDI, and potential were the same as in Example 1. The method for detecting the encapsulation rate was as follows.
[0072] 1.5 ml of the polymer-coated nanoparticle solution of the embodiment was taken and loaded into an ultrafiltration centrifuge tube (Amicon Ultra-4 Centrifugal Filters, molecular weight cutoff 3 kD), centrifuged at 5000 rpm / min, and the free drug in the centrifuge tube was collected. The total drug concentration and the free drug concentration were measured by ICP-MS, and the total drug concentration was 0.51247 mg / ml and the free drug concentration was 0.065258 mg / ml. (The formula for calculating the encapsulation rate is encapsulation rate (EE%) = (total drug concentration - free drug concentration) / total drug concentration x 100%), and the results are shown in Table 3 below. EXAMPLES
[0073] Preparation method: 14 mg of amikacin sulfate and 17 mg of sucrose sodium octasulfate were dissolved in 10 ml of water to obtain solution 1. 129 mg of polysorbate 20 were dissolved in 30 ml of water to obtain solution 2. Using a microfluidics device, solutions 1 and 2 were mixed at a rate of 6 ml / min. The mixed solution was sterilized and filtered to obtain amikacin polymer-coated nanoparticles.
[0074] Stability test: Physiological conditions (pH 7.4, 10 mM phosphate + 150 mM NaCl) were simulated, and the freeze-dried powder of the polymer-coated nanoparticles of the embodiment was redissolved in a solution under the simulated physiological conditions and left at 37°C for 3 days to examine the in vitro stability of the polymer-coated nanoparticles.
[0075] Detection methods: The methods for detecting the particle size, PDI, and potential were the same as in Example 1. The method for detecting the encapsulation rate was as follows.
[0076] 1.5 ml of the polymer-coated nanoparticle solution of the example was taken and loaded into an ultrafiltration centrifuge tube (Amicon Ultra-4 Centrifugal Filters, molecular weight cutoff 3 kD), centrifuged at 5000 rpm / min, and the free drug in the centrifuge was collected. The total drug concentration and the free drug concentration in the centrifuge tube were measured by the HLPC method. The mobile phase consisted of 80% aqueous solution and 20% acetonitrile. Potassium dihydrogen phosphate (1.36 g) and sodium heptanesulfonate (1 g) were dissolved in 1000 ml of ultrapure water, and the pH was adjusted to 3.0 with phosphoric acid to prepare an aqueous phase. The detection wavelength was 200 nm, the flow rate was 1.0 ml / min, and the injection volume was 20 μl. The total drug concentration was 0.35452 mg / ml (day 0), the free drug concentration was 0.36405 mg / ml (day 3), and the free drug concentration was 0.0020755 mg / ml (day 0) and 0.0052642 mg / ml (day 3). (The formula for calculating the encapsulation rate was encapsulation rate (EE%) = (total drug concentration - free drug concentration) / total drug concentration × 100%). The results are shown in Table 3 below. EXAMPLES
[0077] Preparation method: 38 mg of octreotide acetate and 18 mg of sodium alginate were dissolved in 10 ml of water to obtain solution 1. 214 mg of polyoxyethylene hydrogenated castor oil was dissolved in 10 ml of water to obtain solution 2. Using a microfluidics device, solutions 1 and 2 were mixed at a rate of 2 ml / min. The mixed solution was sterilized and filtered to obtain octreotide polymer-coated nanoparticles.
[0078] Stability considerations: Same as in Example 4. Detection methods: The methods for detecting the particle size, PDI, and potential were the same as in Example 1. The method for detecting the encapsulation rate was as follows.
[0079] 1.5 ml of the polymer-coated nanoparticle solution of the embodiment was taken and loaded into an ultrafiltration centrifuge tube (Amicon Ultra-4 Centrifugal Filters, molecular weight cutoff 3 kD), and centrifuged at 5000 rpm / min to collect the free drug in the centrifuge tube. The total drug concentration and the free drug concentration in the centrifuge tube were measured by HLPC method. Tetramethylammonium hydroxide solution (20 ml of 10% tetramethylammonium hydroxide solution was taken, 880 ml of water was added, and the pH value was adjusted to 5.4 with 10% phosphoric acid solution)-acetonitrile (900:100) was used as mobile phase A, and tetramethylammonium hydroxide solution (20 ml of 10% tetramethylammonium hydroxide solution was taken, 380 ml of water was added, and the pH value was adjusted to 5.4 with 10% phosphoric acid solution)-acetonitrile (400:600) was used as mobile phase B, with a flow rate of 1.0 ml / min, and gradient elution was performed according to Table 1. The detection wavelength was 210 nm, the flow rate was 1.0 ml / min, and the injection volume was 20 μl. The total drug concentrations were 1.9182 mg / ml (day 0) and 1.8937 mg / ml (day 3), and the free drug concentrations were 0.040467 mg / ml (day 0) and 0.065353 mg / ml (day 3). (The formula for calculating the encapsulation rate was encapsulation rate (EE%) = (total drug concentration - free drug concentration) / total drug concentration × 100%). The results are shown in Table 3 below.
[0080] Table 1 Gradient elution [Table 1] EXAMPLES
[0081] Preparation method: 24 mg of clindamycin hydrochloride and 72 mg of xanthan gum were dissolved in 10 ml of water to obtain solution 1. 156 mg of PEG-PLA was dissolved in 20 ml of water to obtain solution 2. Solutions 1 and 2 were mixed at a speed of 16 ml / min using a jet flow device. The mixed solution was sterilized and filtered to obtain clindamycin polymer-coated nanoparticles.
[0082] Detection methods: The methods for detecting the particle size, PDI, and potential were the same as in Example 1. The method for detecting the encapsulation rate was as follows.
[0083] 1.5 ml of the polymer-coated nanoparticle solution of the embodiment was taken and loaded into an ultrafiltration centrifuge tube (Amicon Ultra-4 Centrifugal Filters, molecular weight cutoff 30 kD), centrifuged at 5000 rpm / min, and the free drug in the centrifuge tube was collected. The total drug concentration and the free drug concentration in the centrifuge tube were measured by the HLPC method. The mobile phase was 6.8 g / L potassium dihydrogen phosphate (pH 7.5)-acetonitrile (55:45), and the flow rate was 1.0 ml / min, the detection wavelength was 210 nm, the flow rate was 1.0 ml / min, and the injection volume was 20 μl. The total drug concentration was 0.81561 mg / ml, and the free drug concentration was 0.012101 mg / ml. (The formula for the encapsulation rate is encapsulation rate (EE%) = (total drug concentration - free drug concentration) / total drug concentration × 100%), and the results are shown in Table 3 below. EXAMPLES
[0084] Preparation method: 57 mg of thymalfasin and 72 mg of CMC-Na were dissolved in 30 ml of water to obtain solution 1. 292 mg of mPEG2000-DSPE (distearoylphosphatidylethanolamine-methoxypolyethyleneglycol2000) was dissolved in 10 ml of water to obtain solution 2. Using a microfluidics device, solutions 1 and 2 were mixed at a rate of 12 ml / min. The mixed solution was sterilized and filtered to obtain thymalfasin polymer-coated nanoparticles.
[0085] Detection methods: The methods for detecting the particle size, PDI, and potential were the same as in Example 1. The method for detecting the encapsulation rate was as follows.
[0086] 1.5 ml of the polymer-coated nanoparticle solution of the embodiment was taken and loaded into an ultrafiltration centrifuge tube (Amicon Ultra-4 Centrifugal Filters, molecular weight cutoff 30 kD), centrifuged at 5000 rpm / min, and the free drug in the centrifuge tube was collected. The total drug concentration and the free drug concentration were measured by the HLPC method. Ammonium phosphate buffer (26.4 g ammonium sulfate, 25 ml phosphoric acid dissolved in water and diluted to 2000 ml)-acetonitrile (90:10) was used as mobile phase A, and ammonium sulfate buffer-acetonitrile (50:50) was used as mobile phase B, the flow rate was 1.0 ml / min, and gradient elution was performed according to Table 2. The detection wavelength was 210 nm, the column temperature was 50 ° C, and the injection volume was 20 μl, and the total drug concentration was 1.4209 mg / ml and the free drug concentration was 0.0033155 mg / ml. (The formula for calculating the encapsulation rate was encapsulation rate (EE%)=(total drug concentration-free drug concentration) / total drug concentration×100%), and the results are shown in Table 3 below.
[0087] Table 2 Gradient elution [Table 2] EXAMPLES
[0088] Preparation method: 12mg of DC cholesterol was dissolved in 10ml of 0.3mg / ml siRNA solution to obtain solution 1. 32mg of DMG-PEG2000 (1,2-dimyristoyl-rac-glycerol-3-methoxypolyethyleneglycol2000) was dissolved in 10ml of water to obtain solution 2. Using a microfluidic device, solutions 1 and 2 were mixed at a rate of 12ml / min. The mixed solution was sterilized and filtered to obtain siRNA polymer-coated nanoparticles.
[0089] Stability considerations: Same as in Example 4.
[0090] Detection methods: The methods for detecting the particle size, PDI, and potential were the same as in Example 1. The method for detecting the encapsulation rate was as follows.
[0091] An appropriate amount of the polymer-coated nanoparticle solution of the embodiment was taken, centrifuged at 10,000 g centrifugal force for 30 minutes, and the supernatant (free drug) was collected. The demulsified polymer-coated nanoparticle solution and the supernatant were mixed with Qubit detection reagent, respectively, and then the total drug concentration and the free drug concentration were measured using an Invitrogen Qubit 4 fluorometer. The total drug concentration was 0.15385 mg / ml (day 0), 0.14840 mg / ml (day 3), and the free drug concentration was 0.037231 mg / ml (day 0), 0.030001 mg / ml (day 3). (The formula for the encapsulation rate is encapsulation rate (EE%) = (total drug concentration - free drug concentration) / total drug concentration × 100%), and the results are shown in Table 3 below. EXAMPLES
[0092] Preparation method: 12 mg of chitosan hydrochloride (CAS number: 70694-72-3) was dissolved in 30 ml of 0.2 mg / ml siRNA solution to obtain solution 1. 52 mg of PEG-cholesterol was dissolved in 10 ml of water to obtain solution 2. Using a microfluidics device, solutions 1 and 2 were mixed at a rate of 6 ml / min. The mixed solution was sterilized and filtered to obtain siRNA polymer-coated nanoparticles.
[0093] Detection method: The total drug concentration was 0.15644 mg / ml and the free drug concentration was 0.037077 mg / ml as measured in the same manner as in Example 8. The results are shown in Table 3 below. EXAMPLES
[0094] Preparation method: 17 mg of polyethyleneimine hydrochloride (CAS number: 49553-93-7) and 14 mg of sodium sulfadiazine were dissolved in 20 ml of water to obtain solution 1. 96 mg of polysorbate 20 was dissolved in 10 ml of water to obtain solution 2. Using a microfluidics device, solutions 1 and 2 were mixed at a rate of 24 ml / min. The mixed solution was sterilized and filtered to obtain sulfadiazine polymer-coated nanoparticles.
[0095] Stability considerations: Same as in Example 4.
[0096] Detection methods: The methods for detecting the particle size, PDI, and potential were the same as in Example 1. The method for detecting the encapsulation rate was as follows.
[0097] 1.5 ml of the polymer-coated nanoparticle solution of the embodiment was taken and loaded into an ultrafiltration centrifuge tube (Amicon Ultra-4 Centrifugal Filters, molecular weight cutoff 3 kD), centrifuged at 5000 rpm / min, and the free drug in the centrifuge tube was collected. The total drug concentration and the free drug concentration were measured by the HLPC method. Using 0.1% phosphoric acid-acetonitrile (85:15) as the mobile phase, the detection wavelength was 270 nm, the column temperature was 40°C, and the injection volume was 20 μl. The total drug concentration was 0.48057 mg / ml (day 0), 0.48896 mg / ml (day 3), and the free drug concentration was 0.017063 mg / ml (day 0), 0.018606 mg / ml (day 3). (The formula for the encapsulation rate is encapsulation rate (EE%) = (total drug concentration - free drug concentration) / total drug concentration × 100%), and the results are shown in Table 3 below. EXAMPLES
[0098] Preparation method: 32 mg of risperidone hydrochloride and 52 mg of sodium carboxymethylcellulose were dissolved in 30 ml of water to obtain solution 1. 291 mg of mPEG2000-DSPE (distearoylphosphatidylethanolamine-methoxypolyethylene glycol 2000) was dissolved in 10 ml of water to obtain solution 2. Using a microfluidics device, solutions 1 and 2 were mixed at a rate of 16 ml / min. The mixed solution was sterilized and filtered to obtain risperidone polymer-coated nanoparticles.
[0099] Detection methods: The methods for detecting the particle size, PDI, and potential were the same as in Example 1. The method for detecting the encapsulation rate was as follows.
[0100] 1.5 ml of the polymer-coated nanoparticle solution of the embodiment was taken and loaded into an ultrafiltration centrifuge tube (Amicon Ultra-4 Centrifugal Filters, molecular weight cutoff 30 kD), centrifuged at 5000 rpm / min, and the free drug in the centrifuge tube was collected. The total drug concentration and the free drug concentration were measured by the HLPC method. Using methanol-0.05 mol / L ammonium acetate solution (pH value adjusted to 6.8 with ammonia test solution) (60:40) as the mobile phase, the detection wavelength was 275 nm, the column temperature was 40° C., and the injection volume was 20 μl. The total drug concentration was 0.81783 mg / ml and the free drug concentration was 0.0088522 mg / ml. (The formula for the encapsulation rate is encapsulation rate (EE%)=(total drug concentration-free drug concentration) / total drug concentration×100%), and the results are shown in Table 3 below. EXAMPLES
[0101] Preparation method: 2 mg of poly-L-arginine hydrochloride (CAS number: 26982-20-7) was dissolved in 10 ml of 0.2 mg / ml mRNA solution to obtain solution 1. 17 mg of PEG-PLA was dissolved in 10 ml of water to obtain solution 2. Using a microfluidics device, solutions 1 and 2 were mixed at a rate of 6 ml / min. The mixed solution was sterilized and filtered to obtain mRNA polymer-coated nanoparticles.
[0102] Stability considerations: Same as in Example 4.
[0103] Detection method: Measurements were performed in the same manner as in Example 8. The total drug concentration was 0.10297 mg / ml (day 0) and 0.10196 mg / ml (day 3), and the free drug concentration was 0.014696 mg / ml (day 0) and 0.011788 mg / ml (day 3). The results are shown in Table 3 below. EXAMPLES
[0104] Preparation method: 32 mg of DOTAP ((2,3-dioleoyl-propyl)-trimethylammonium chloride) was dissolved in 5 ml of 50% aqueous ethanol, and the resulting solution was mixed with 30 ml of 0.1 mg / ml aqueous mRNA solution to obtain solution 1. 48 mg of mPEG2000-DSPE was dissolved in 5 ml of water to obtain solution 2. Using a microfluidics device, solutions 1 and 2 were mixed at a rate of 4 ml / min, and ethanol was removed and buffer exchange was performed by dialysis twice with 200 volumes of PBS at pH 7.4 using a 10 kD regenerated cellulose dialysis membrane. The first time was at room temperature for 3 hours, and the final time was at 4 °C overnight. After sterilization and filtration, mRNA polymer-coated nanoparticles were obtained.
[0105] Detection method: Measurements were performed in the same manner as in Example 8, and the total drug concentration was 0.077670 mg / ml, and the free drug concentration was 0.0083707 mg / ml. The results are shown in Table 3 below.
[0106] [Comparative Example 1] Preparation method: 20 mg of colistin sulfate was dissolved in 40 ml of water, 600 mg of mPEG5000-DSPE was added and dissolved, and then 32 mg of polyglutamic acid was added. The mixture was dispersed using a high-pressure homogenizer, and then sterilized and filtered to obtain colistin polymer-coated nanoparticles.
[0107] Detection method: Measurement was performed in the same manner as in Example 1, and the amount of fractionated drug was 0.52187 mg, and the amount of free drug was 0.77657 mg. The results are shown in Table 3 below.
[0108] [Comparative Example 2] Preparation method: 20 mg of polymyxin B sulfate and 72 mg of sodium hyaluronate were dissolved in 20 ml of water, and the solution was sterilized and filtered to obtain polymyxin B nanoparticles.
[0109] Detection method: Measurement was performed in the same manner as in Example 1, and the amount of fractionated drug was 0.61199 mg, and the amount of free drug was 1.8497 mg. The results are shown in Table 3 below.
[0110] [Comparative Example 3] Preparation method: 14 mg of amikacin sulfate was dissolved in 10 ml of water to obtain solution 1. 427 mg of polyoxyethylene hydrogenated castor oil was dissolved in 30 ml of water to obtain solution 2. Using a microfluidics device, solutions 1 and 2 were mixed at a rate of 6 ml / min. The mixed solution was sterilized and filtered to obtain amikacin sulfate polymer-coated nanoparticles.
[0111] Stability considerations: Same as in Example 4.
[0112] Detection method: Measurements were performed in the same manner as in Example 4. The total drug concentration was 0.35388 mg / ml (day 0) and 0.34329 mg / ml (day 3), and the free drug concentration was 0.30611 mg / ml (day 0) and 0.32767 mg / ml (day 3). The results are shown in Table 3 below.
[0113] [Comparative Example 4] Preparation method: 10 mg of oxaliplatin was dissolved in 20 ml of water to obtain solution 1. 120 mg of DSPC, 40 mg of cholesterol, and 40 mg of mPEG2000-DSPE were dissolved in 10 ml of absolute ethanol to obtain solution 2. Using a microfluidics device, solutions 1 and 2 were mixed at a rate of 9 ml / min. Using a 30 kD regenerated cellulose dialysis membrane, ethanol was removed by dialysis twice against 50 times the amount of 1% sucrose solution to exchange the buffer solution. The first time was at room temperature for 3 hours, and the final time was at 4°C overnight. After sterilization and filtration, oxaliplatin liposomes were obtained.
[0114] Detection method: Measurements were performed in the same manner as in Example 3, and the total drug concentration was 0.34389 mg / ml and the free drug concentration was 0.31005 mg / ml. The results are shown in Table 3 below.
[0115] [Comparative Example 5] Preparation method: 38 mg of octreotide acetate and 18 mg of sodium alginate were dissolved in 10 ml of water to obtain solution 1. 14 mg of anionic surfactant sodium dodecyl sulfate was dissolved in 10 ml of water to obtain solution 2. Using a microfluidics device, solutions 1 and 2 were mixed at a rate of 9 ml / min. The mixed solution was sterilized and filtered to obtain octreotide nanoparticles.
[0116] Stability considerations: Same as in Example 4.
[0117] Detection method: Measurements were performed in the same manner as in Example 5. The total drug concentration was 1.9735 mg / ml (day 0) and 1.9411 mg / ml (day 3), and the free drug concentration was 0.028523 mg / ml (day 0) and 0.88104 mg / ml (day 3). The results are shown in Table 3 below.
[0118] [Comparative Example 6] Preparation method: 10ml of 0.3mg / ml siRNA solution was taken as solution 1, and 32mg of DMG-PEG2000 was dissolved in 10ml of water to obtain solution 2. Using a microfluidic device, solutions 1 and 2 were mixed at a rate of 12ml / min. The mixed solution was sterilized and filtered to obtain siRNA polymer-coated nanoparticles.
[0119] Detection method: Measurements were performed in the same manner as in Example 8, and the total drug concentration was 0.15010 mg / ml and the free drug concentration was 0.14412 mg / ml. The results are shown in Table 3 below.
[0120] [Comparative Example 7] Preparation method: The siRNA solution was diluted to 0.1mg / ml with 50mM pH4 sodium citrate buffer to obtain solution 1. DOTAP, DOPE (dioleoylphosphatidylethanolamine), cholesterol and DMG-PEG2000 were mixed in a ratio of 50:10:38.5:1.5 and dissolved in absolute ethanol to obtain a 50mM lipid ethanol solution as solution 2. Using a microfluidics device, solutions 1 and 2 were mixed at a rate of 18ml / min. The volume ratio of solutions 1 and 2 was 3:1. Using a 10kD regenerated cellulose dialysis membrane, the ethanol was removed by dialysis twice with 200 times the amount of PBS at pH7.4, and the buffer was exchanged. The first time was at room temperature for 3 hours, and the final time was overnight at 4°C. After sterilization and filtration with a filter membrane, siRNA lipid nanoparticles were obtained.
[0121] Detection method: Measurements were performed in the same manner as in Example 8. The total drug concentration was 0.077142 mg / ml, and the free drug concentration was 0.0020593 mg / ml. The results are shown in Table 3 below.
[0122] 1. Performance indicators The performance parameters of the polymer-coated nanoparticles (average particle size, polydispersity index PDI, zeta potential, encapsulation rate) were measured according to the methods described in each of the examples and comparative examples. The results are shown in Table 3 below.
[0123] Table 3. Performance data of polymer-coated nanoparticles [Table 3]
[0124] Stability considerations: To simulate physiological conditions (pH 7.4, 10 mM phosphate + 150 mM NaCl), the freeze-dried powder of the polymer-coated nanoparticles of the examples was redissolved in a solution under simulated physiological conditions and left at 37°C for 3 days to examine the in vitro stability of the polymer-coated nanoparticles.
[0125] Table 4. Performance and stability data for polymer-coated nanoparticles [Table 4]
[0126] 2. Example of Effects (1) Antibacterial activity test of the polymer-coated nanoparticles of Examples 1 and 2 and Comparative Examples 1 and 2 A total of 44 clinically isolated Gram-negative bacilli, including 12 Escherichia coli (carbapenem-susceptible), 12 Klebsiella pneumoniae (carbapenem-susceptible), 10 Acinetobacter baumannii (carbapenem-susceptible), and 10 Pseudomonas aeruginosa (carbapenem-susceptible), were collected and tested for drug susceptibility.
[0127] The minimum inhibitory concentrations (MICs) of test substances against clinical isolates were determined by the broth microdilution method according to the recommendations of the Clinical and Laboratory Standards Institute (CLSI) 2021 version.
[0128] (1) Preparation of antibiotics: The test drugs were dissolved and diluted, and the control drugs were dissolved and diluted according to the requirements of CLSI. The test concentration range of the antibiotic solutions was 0.015 mg / L to 32 mg / L. (2) Culture medium: Cation adjusted-Mueller Hinton broth (CAMHB), manufactured by American BD, lot number: 9324795. (3) Inoculum amount: Fresh and pure colonies were collected from Columbia blood cold by direct colony suspension method, adjusted to 0.5 McFarland turbidity, and then appropriately diluted to give a final concentration of the test bacteria of 105 CFU / mL. (4) Culture conditions: Cultured in air at 35°C ± 2°C for 16 to 20 hours. (5) Reading and judging the results: According to the European EUCAST breakpoint criteria, colistin ≤ 2 mg / L was judged as susceptible, and ≥ 4 mg / L was judged as resistant. The lowest antibiotic concentration that inhibited bacterial growth was read as the MIC value. (6) Quality control strains: Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATCC 27853. (7) Data statistics: Statistical analysis of drug susceptibility test results was performed using WHONET 5.6 version software.
[0129] Table 5. In vitro drug susceptibility test of test drugs against 12 strains of E. coli (MIC mg / L) [Table 5]
[0130] Table 6. In vitro drug susceptibility test of test drugs against 12 strains of Klebsiella pneumoniae (MIC mg / L) [Table 6]
[0131] Table 7. In vitro drug susceptibility test of test drugs against 10 strains of Acinetobacter baumannii (MIC mg / L) [Table 7]
[0132] Table 8. In vitro drug susceptibility test of test drugs against 10 strains of Pseudomonas aeruginosa (MIC mg / L) [Table 8]
[0133] Table 9. In vitro drug susceptibility test of test drugs against 44 strains of Gram-negative bacilli (MIC mg / L) [Table 9]
[0134] As can be seen from the above results, the antibacterial activities of Examples 1 and 2 against gram-negative bacilli are superior to colistin sulfate, while the antibacterial activities of Comparative Examples 1 and 2 against gram-negative bacilli are equivalent to or slightly lower than colistin sulfate. This indicates that the polymer-coated nanoparticles of the present invention significantly improve the antibacterial activity of the drug, while the antibacterial activity of Comparative Example 1 against gram-negative bacilli is not significantly different from that of colistin sulfate, and the antibacterial activity of Comparative Example 2 against gram-negative bacilli is slightly weaker than that of colistin sulfate.
[0135] (2) Consideration of safety test of polymer-coated nanoparticles in Examples 1 and 2 and Comparative Examples 1 and 2 The drug safety of colistin sulfate, nanoparticles of Examples 1 and 2, and Comparative Examples 1 and 2 in mice was compared. Male ICR mice (purchased from Shanghai Lingcheng Experimental Animal Co., Ltd.) aged 7-8 weeks and weighing 25-30 g were administered colistin sulfate or polymyxin polymer-coated nanoparticle solutions by intravenous injection. The drug concentration was 1.5 mg / ml, the dosage range was 8-60 mg / kg, and the administration volume was adjusted according to the animal's weight. The highest dose that allows sustained survival of all subjects in the experiment is defined as the MTD.
[0136] Animal grouping: Before the start of dosing, the animals were weighed and randomly grouped according to their body weight. Experimental endpoints: clinical observations, animal morbidity / mortality, and body weight change. The maximum tolerated dose was the highest dose of compound that could reduce the body weight of mice by 20% or less without animal mortality. The results are shown in the table below.
[0137] Table 10. Safety test results [Table 10]
[0138] Based on the above results, the maximum tolerated doses of the polymer-coated nanoparticles of Examples 1 and 2 in mice were much higher than that of colistin sulfate, while the maximum tolerated doses of the polymer-coated nanoparticles of Comparative Examples 1 and 2 were equivalent to that of colistin sulfate. The above results showed that the polymer-coated nanoparticles of the present invention could significantly improve the safety of drugs in mice, and also showed that the safety of drugs with a narrow therapeutic window was significantly improved.
[0139] (3) The effect of Example 3 on the in vitro proliferation of HT29 cells is examined, and the IC50 activity value of the test substance is determined.
[0140] Cell culture: HT29 (catalog number: CBP30001L, purchased from Cobioer) was revived and cultured in 1640 + 10% FBS.
[0141] Plating: The normally grown cells were taken, digested with trypsin cell digestion solution, centrifuged, counted, and plated in a 96-well plate at a cell density of 3000 cells / well, 100 μL per well, 60 wells in total. Appropriate amount of PBS was used to seal the edges of the wells to prevent water from evaporating.
[0142] Dosing: Dosing was performed the next day after cell plating. 100 μL of drug solution was added to each well, with two duplicate wells for each concentration point.
[0143] Detection: 72 hours after drug treatment, all the liquid in the 96-well plate was poured out, and 100 μL CCK8 solution (diluted 1:9 with medium) was added to each well. After incubation at 37°C for a certain period (OD450 of the vehicle group reached 1.0 or more), the absorbance at 450 nm was detected using a microplate reader.
[0144] Data processing: Inhibition rate (%) = (1-OD450 Sample / OD450 Vehicle )*100.OD450 Sample is the 450 nm absorbance value of the drug treatment group, and OD450Vehicle was the 450 nm absorbance value of the DMSO control group. Using GraphPad Prism 8.0 software, S-shaped dose-survival curves were plotted using a nonlinear regression model, and IC50 values were calculated.
[0145] Test Results: Table 11 IC50 activity values [Table 11]
[0146] The above results showed that the inhibitory effect of the polymer-coated nanoparticles of the present invention on the in vitro proliferation of HT-29 cells was stronger than that of cyclohexanediamineplatinum dihydrate.
[0147] (4) Safety Test Considerations for Polymer-Coated Nanoparticles in Example 3 Male Balb / c nude mice (purchased from Shanghai Lingchun Laboratory Animal Co., Ltd.), aged 6-7 weeks and weighing 17-21 g, were intravenously injected with cyclohexanediamineplatinum dihydrate or cyclohexanediamineplatinum dihydrate polymer. The drug concentration was 1.0 mg / ml, and the administration volume was adjusted according to the animal's body weight. The highest dose that allows sustained survival of all subjects in the experiment is defined as the MTD.
[0148] Animal grouping: Before the start of dosing, the animals were weighed and randomly grouped according to their body weight. Experimental parameters: After administration, the observation intervals and frequency were appropriately set to observe the time to onset of toxic reactions, recovery time, and animal death time, and the observation was continued for at least 14 days. If the onset of toxic reactions or recovery is slow, the observation time should be appropriately extended. The results are shown in the table below.
[0149] Table 12 Experimental results [Table 12]
[0150] The results showed that the mice's tolerance to the polymer-coated nanoparticles of Example 3 was much higher than that to cyclohexanediamineplatinum dihydrate, indicating that the polymer-coated nanoparticles of the present invention greatly improved the safety of cyclohexanediamineplatinum dihydrate.
[0151] (5) Consideration of in vitro release of Examples 4, 5, 6, 7, and 11 1.5 ml of the polymer-coated nanoparticle solution was taken and placed in a dialysis bag (molecular weight cutoff: 100 kD). The dialysis bag was placed in a centrifuge tube containing 18.5 ml of PBS (pH 7.4, 10 mM phosphate + 150 mM NaCl) and shaken in a 37°C thermostatic water bath shaker (100 rpm). Sampling was performed at regular intervals, and the dialysis bag was transferred to a new medium to measure the concentration of the free drug outside the dialysis bag by HPLC, and the release degree of the polymer-coated nanoparticles at each time point was calculated. The release curve is shown in Figure 10.
[0152] The polymer-coated nanoparticles provided by the present invention can be released sustainedly and stably in PBS (pH 7.4, 10 mM phosphate + 150 mM NaCl) buffer solution.
[0153] The above detailed description is a specific description of one of the promising embodiments of the present invention, and such embodiment is not intended to limit the patent scope of the present invention, and equivalent embodiments or modifications without departing from the present invention should be included within the scope of the technical proposal of the present invention.
Claims
1. 1. A polymer-coated nanoparticle having a composition structure consisting of a hydrophilic aggregate core and a coating of a polymer molecular material containing polyoxyethylene structural units, the hydrophilic aggregate core comprises a cationic component and an anionic component as raw materials for production, the cationic component being a cation or a compound ionizable to a cation or a composition thereof, and the anionic component being an anion or a compound ionizable to an anion or a composition thereof; The cationic compound or composition thereof is any one or more selected from hydrophilic small molecule compounds or polypeptides that are ionizable or have a net positive charge.
2. 2. The polymer-coated nanoparticles of claim 1, wherein the nanoparticles have a particle size of 10-400 nm, a PDI<0.5, a weakly or neutral surface, a surface potential range of -40 mV to 40 mV, and an encapsulation rate of >60%.
3. the polypeptide is a hydrophilic polypeptide having an ionizable or positive net charge and a molecular weight of <10,000; The ionizable or positively charged hydrophilic small molecule compound is an ionizable or positively charged hydrophilic compound that contains an amine group structure. The polymer-coated nanoparticle of claim 1 .
4. The polypeptides include any one or more of ionizable hydrophilic polypeptides and derivatives thereof having a cyclic structure containing a free amine group, ionizable hydrophilic polypeptides and derivatives thereof having a molecular weight of <10,000 and free primary amine, secondary amine, or tertiary amine structures, polylysine and derivatives thereof, polyarginine and derivatives thereof, polyhistidine and derivatives thereof, and arginine-rich polypeptides. The polymer-coated nanoparticles of claim 3 .
5. The polypeptide is selected from polymyxin and its derivatives, daptomycin, vancomycin, tigecycline, thymalfasin, octreotide acetate, liraglutide, pasireotide; The polymer-coated nanoparticles of claim 4.
6. The hydrophilic small molecule compound having an ionizable or positive net charge is one or more of metal complexes and derivatives thereof, ionizable hydrophilic anesthetic / analgesic drugs having an amine group structure, ionizable hydrophilic psychotropic drugs having an amine group structure, and ionizable hydrophilic anticancer / antitumor drugs having an amine group structure and derivatives thereof, as well as imipenem, clindamycin hydrochloride, and amikacin sulfate. The polymer-coated nanoparticle of claim 1 .
7. The metal complex and its derivative are selected from platinum complexes and their derivatives, ruthenium (II) complexes and their derivatives, and vanadium complexes and their derivatives; The ionizable hydrophilic anesthetic / analgesic drug having an amine group structure is selected from clonidine hydrochloride, pregabalin; The ionizable hydrophilic psychotropic drug having an amine group structure is selected from risperidone hydrochloride, methylphenidate, levetiracetam, and brivaracetam; The ionizable hydrophilic anticancer / antitumor drug having an amine group structure and its derivatives are selected from bortezomib, imatinib, and palbociclib. The polymer-coated nanoparticles of claim 6.
8. The anionic compound or composition thereof is any one or more of ionizable or anionic hydrophilic small molecule compounds, ionizable or anionic hydrophilic monosaccharide or oligosaccharide acids and derivatives thereof, ionizable or anionic hydrophilic polysaccharides and derivatives thereof, anionic polyamino acids and derivatives thereof, and nucleic acids. The polymer-coated nanoparticle of claim 1 .
9. The monosaccharide or oligosaccharide acid and its derivatives include any one or more of sulfated glucose, sulfated fructose, phosphorylated glucose, phosphorylated fructose, sulfated sucrose, sulfated lactose, sulfated trehalose, phosphorylated sucrose, phosphorylated lactose and phosphorylated trehalose; The polymer-coated nanoparticles of claim 8.
10. The polysaccharide and its derivative are one or more of glycosaminoglycan, cellulose polysaccharide, polyuronic acid polysaccharide, galactomannan polysaccharide, and derivatives thereof. The polymer-coated nanoparticles of claim 9.
11. The glycosaminoglycan is one or more of sodium hyaluronate, cross-linked sodium hyaluronate, chondroitin sulfate, dermatan sulfate, keratan sulfate, heparin sodium, heparan sulfate, dalteparin sodium, enoxaparin sodium, and fondaparinux; The polymer-coated nanoparticles of claim 10.
12. The cellulose-based polysaccharide is one or more of cellulose acetate, sodium carboxymethylcellulose, hydroxyethylcellulose, hydroxyethylmethylcellulose, hydroxypropylcellulose, and hypromellose. The polymer-coated nanoparticles of claim 10.
13. The polyuronic acid polysaccharide, galactomannan polysaccharide, and derivatives thereof are one or more of polyglucuronic acid, polyfurfural acid, sodium polymannuronate, sodium polyguluronic acid, alginic acid, sodium alginate, propylene glycol alginate, xanthan gum, tragacanth, gum arabic, and carrageenan. The polymer-coated nanoparticles of claim 10.
14. The nucleic acid is a ribonucleic acid or a deoxyribonucleic acid, and includes one or more of siRNA, mRNA, miRNA, antisense oligonucleotide, DNA, circular RNA, and tRNA; The polymer-coated nanoparticles of claim 8.
15. The anion component includes one or more of polyglutamic acid polypeptides and derivatives thereof, polyaspartic acid polypeptides and derivatives thereof, hyaluronate, sucrose octasulfate, sodium alginate, xanthan gum, CMC-Na, siRNA, mRNA, sodium sulfadiazine, and sodium carboxymethylcellulose; The polymer-coated nanoparticles according to any one of claims 1 to 14.
16. The polyoxyethylene structural unit is —(CH 2 CH 2 O) n (n = 6 to 460); The polymer-coated nanoparticle of claim 1 .
17. The polymer molecule material containing a polyoxyethylene structural unit is one or more of PEG-phospholipid, PEG-cholesterol, PEG-polymer, polysorbate, polyoxyethylene castor oil and its derivatives, and polyoxyethylene stearate; The polymer-coated nanoparticle of claim 1 .
18. The polymeric material comprising polyoxyethylene structural units includes any one or more of distearoylphosphatidylethanolamine-methoxypolyethylene glycol, PEG-PLA, 1,2-dimyristoyl-rac-glycerol-3-methoxypolyethylene glycol, polyethylene glycol-polylactic acid-glycolic acid polymer, polyglutamic acid-polyethylene glycol-carboxylic acid, polysorbate, polyoxyethylene castor oil, polyoxyethylene stearate, polyethylene glycol-polyglutamic acid, polyethylene glycol-glyceryl dipalmitate, polyethylene glycol-dipalmitoylphosphatidylethanolamine, polyethylene glycol-dimyristoylphosphatidylethanolamine, polyethylene glycol-dilauroylphosphatidylethanolamine, polyethylene glycol-dipalmitoylphosphatidylserine, polyethylene glycol-cholesterol, and cholesterol-polyethylene glycol-VA.
20. The polymer-coated nanoparticle of claim 17.
19. The charge ratio of the cationic component to the anionic component in the nanoparticles is 1-8:1-10; The weight percentage of the hydrophilic aggregate core in the nanoparticles is between 1% and 90%, preferably between 5% and 80%; The polymer-coated nanoparticle of claim 1 .
20. A method for producing the polymer-coated nanoparticles according to claims 1 to 19, comprising the steps of: (1) preparing an aggregate solution by dissolving and mixing a cationic component and an anionic component; (2) preparing a coating solution by dissolving a polymer molecule material containing polyoxyethylene structural units; (3) mixing the aggregate solution with the coating solution to prepare a polymer-coated nanoparticle solution; A method for producing polymer-coated nanoparticles, comprising:
21. further filtering and / or purifying the polymer-coated nanoparticle solution; The method for producing the polymer-coated nanoparticles according to claim 20.
22. In the method for producing nanoparticles, the aggregate solution is a homogeneous solution, and the mixing volume ratio of the aggregate solution to the coating solution is 1-10:1-20; The method for producing the polymer-coated nanoparticles according to claim 20.
23. In the method for producing the nanoparticles, the mixing is performed by using a microchannel mixing method, and the microchannel mixing method is performed by using an injection technique, a microfluidics technique, or a jet flow technique; The method for producing the polymer-coated nanoparticles according to claim 20.
24. In the above-mentioned manufacturing method, The mixing speed of the microchannel mixing is 0.5 to 400 ml / min; The method for producing the polymer-coated nanoparticles according to claim 23.
25. A preparation of polymer-coated nanoparticles according to any one of claims 1 to 19 or of nanoparticles obtained by the method for producing polymer-coated nanoparticles according to any one of claims 20 to 24, The nanoparticles have a structure comprising a hydrophilic aggregate core containing the active ingredient and a polymer molecular coating containing polyoxyethylene structural units; The encapsulation rate of the nanoparticles is >60%, the average particle size is 10-400 nm, the surface is weakly or neutrally charged, and the surface potential range is -40 mV to 40 mV; Nanoparticle formulations.
26. Contains excipients commonly used in pharmacy, The excipient includes one or more of potassium dihydrogen phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, dipotassium hydrogen phosphate, sodium chloride, potassium chloride, sodium acetate, acetic acid, sucrose, mannitol, lactose, glucose, trehalose, polyethylene glycol, glycerin, phosphate, acetate, amino acid, water for injection, 0.5 to 0.9% sodium chloride aqueous solution, 1 to 5% glucose aqueous solution, and PBS buffer solution; 26. A formulation of the nanoparticles described in claim 25.
Citation Information
Patent Citations
Method for producing polymeric micelles containing anionic drugs
JP2019501900A
Therapeutic nanoparticles via coacervate complexation and their use to treat bacteria
JP2021532192A